Estudo da angiogênese pelo CD105 e FvW no carcinoma epidermóide oral e sua relação com o estadiamento clínico do tumor - Xavier, Ruth Lopes de Freitas (2008)
The purpose of this study was to assess the immunohistochemical expression of CD105 and FvW antibodies in the angiogenesis of oral epidermoid carcinoma (OEC), correlating it with the TNM clinical staging system, seeking a better understanding of its biological behavior and use as an indicator of prognosis.The sample consisted of 30 epidermoid carcinoma (EC) cases, 10 of the floor of the mouth, 10 of the retromolar region and 10 of the tongue, in addition to 10 cases of pyogenic granuloma, which made up the control group. The results showed that mean microvessel counts (MVC) were correspondingly higher in the pyogenic granuloma group (CD105 = 57.26 vessels and FvW = 39.64) than in the EC group (CD105 = 10.09 and FvW = 12.20) and that the differences were statistically significant between the groups for each of the angiogenic biomarkers (p = 0.002 for CD105 and p< 0.001 for FvW). CD105 had better positivity in the pyogenic granuloma group (mean = 57.26 vessels) and for EC, FvW had the highest expression (mean = 12.20 vessels). With respect to EC, the most affected age group was between 51 and 70 years (n = 14; 46.7%), with a representative MVC for both markers. No statistically significant difference was found between the sexes for any of the markers (p = 0.967 for CD105 and p = 0.744 for FvW). Mean CD105 levels were much higher in patients with stage T3 and T4 (17.13) and lower in those with stage N+ (6.36). Mean FvW levels were higher in the patients with stage T1 and T2 (12.23) and lower in patients with T3 and T4 (12.10), but without a statistically significant difference. In regard to anatomic location, a statistically significant difference was observed between FvW sites, with a statistically significant difference between floor of the mouth cases and those located in the retromolar region (p =0.013). Therefore, this study suggests that CD105 expression in OEC angiogenesis, in contrast to other types of malignant neoplasias, may not be correlated with prognosis and tumor aggressiveness, whereas FvW was a more effective antibody for staining this lesion